The changing face of risk factors for non-communicable disease in Myanmar: findings from the 2009 and 2014 WHO STEP Surveys. (15th October 2018) - Grover, Shekhar; Sinha, Dhirendra N; Gupta, Sanjay; Gupta, Prakash C; Mehrotra, Ravi
Abstract: Background: Myanmar is burdened with the dual problem of communicable and non-communicable diseases (NCD), and is constantly endeavoring to attain its health objectives with limited resources. This study compares the results for the 2009 and 2014 WHO STEPs surveys (the 'stepwise' approach to adult risk factor surveillance) in Myanmar to determine the change in NCD risk factors over time. Methodology: The proportion of individuals with major NCD risk factors such as current tobacco and alcohol consumption, <5 fruit/vegetable servings, physical activity, raised blood pressure (BP) and overweight and obesity from the year 2009 ( n = 6414) and year 2014 ( n = 8757) WHO STEP surveys were compared for the age group 25–64 and relative changes (RC) calculated. Results: Tobacco and alcohol consumption has increased significantly (25 and 49% RC, respectively) over the years. Individuals with low fruit/vegetable consumption (<5 servings) have declined (4.3% RC) and physical activity has increased significantly (46.5% RC). The prevalence of overweight, obese and hypertensive individuals has reduced significantly during this period with a RC reduction of 18, 28 and 20%, respectively. Conclusion: Reductions in some NCD risk factors are encouraging but control of tobacco use and alcohol consumption requires more stringent policies in order to prevent NCDs in the future.